Displacement of the hyoid bone by muscle paralysis and lung volume increase: the effects of obesity and obstructive sleep apnea. Issue 1 (29th October 2018) - Kohno, Akane; Kitamura, Yuji; Kato, Shinichiro; Imai, Hirohisa; Masuda, Yoshitada; Sato, Yasunori; Isono, Shiroh
Abstract: Study Objectives: Animal studies suggest a pivotal role of the hyoid bone in obstructive sleep apnea (OSA). We aimed to explore the role of the hyoid bone in humans by testing the hypotheses that muscle paralysis and lung volume (LV) changes displace the hyoid bone position particularly in people with obesity and/or OSA. Methods: Fifty patients undergoing general anesthesia participated in this study (20 participants with nonobese, non-OSA; 8 people with nonobese OSA; and 22 people with obese OSA). Three lateral neck radiographs to assess the hyoid position (primary variable) and craniofacial structures were taken during wakefulness, complete muscle paralysis under general anesthesia, and LV increase under general anesthesia. LV was increased by negative extrathoracic pressure application and LV changes were measured with a spirometer. Analysis of covariance was used to identify statistical significance. Results: Muscle paralysis under general anesthesia significantly displaced the hyoid bone posteriorly (95% CI: 1.7 to 4.6, 1.5 to 5.2, and 1.1 to 4.0 mm in nonobese non-OSA, nonobese OSA, and obese OSA groups, respectively), and this was more prominent in people with central obesity. LV increase significantly displaced the hyoid bone caudally in all groups (95% CI: 0.2 to 0.7, 0.02 to 0.6, and 0.2 to 0.6 mm/0.1 liter LV increase in nonobese non-OSA, nonobese OSA, and obese OSA groups, respectively). Waist–hip ratio was directly associated with the caudal displacement during LV increase. Conclusions: The hyoid bone plays an important role in the pathophysiology of pharyngeal airway obstruction due to muscle paralysis and LV reduction, particularly in people with obesity. Clinical Trial: UMIN Clinical Trial Registry, https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=cR000022635&language=E, UMIN000019578